Enlightening the dynamical evolution of Galactic open clusters: an approach using Gaia DR3 and analytical descriptions - Angelo, M S; Santos Jr, J F C; Maia, F F S; Corradi, W J B (Monthly notices of the Royal Astronomical Society, 2023)
ABSTRACT Most stars in our Galaxy form in stellar aggregates, which can become long-lived structures called open clusters (OCs). Along their dynamical evolution, their gradual depletion leave some imprints on their structure. In this work, we employed astrometric, photometric, and spectroscopic data from the Gaia DR3 catalogue to uniformly characterize a sample of 60 OCs. Structural parameters (tidal, core, and half-light radii, respectively, rt, rc, and rh), age, mass (Mclu), distance, reddening, Jacobi radius (RJ), and half-light relaxation time (trh) are derived from radial density profiles and astrometrically decontaminated colour–magnitude diagrams. Ages and Galactocentric distances (RG) range from 7.2$\, \lesssim \,$log(t.yr$^{-1})\, \lesssim \,$9.8 and 6$\, \lesssim \, R_G$(kpc)$\, \lesssim \,$12. Analytical expressions derived from N-body simulations are also employed to estimate the OC initial mass (Mini) and mass loss due to dynamical effects. Both rc and the tidal filling ratio, rh/RJ, decrease with the dynamical age (= t/trh), indicating the shrinking of the OCs’ internal structure as consequence of internal dynamical relaxation. This dependence seems differentially affected by the external tidal field, since OCs at smaller RG tend to be dynamically older and have smaller Mclu/Mini ratios. For $R_G\lesssim 8\,$ kpc, the rh/RJ ratio presents a slight positive correlation with RG. Beyond this limit, there is a dichotomy in which more massive OCs are more compact and less subject to tidal stripping compared to those less massive and looser OCs at similar RG. Besides, the rt/RJ ratio also correlates positively with RG.